The Effect of Concentrated Seawater Salinity on Soybean Protein Coagulation in Tofu Production - Rohmawati, Manis; Muflihah, Yeni Maulidah; Handayani, Wuryanti; Asnawati; Mulyono, Tri (Department of Chemistry, Faculty of Mathematics and Natural Sciences, University of Jember, 2025)
Seawater, which has a salinity of 35 ‰, contains essential ions such as chloride, sodium, sulfate, magnesium, and calcium. These ions play a crucial role in the coagulation of proteins. Salt-based coagulants are among the oldest and most commonly used in tofu production. Additionally, several metal cations exhibit similar coagulating effects on soybean proteins. Tofu can be produced by adding salt coagulants, like calcium sulfate (commonly known as tofu stone) and seawater extract. The seawater extract was obtained from seawater through evaporation in three distinct ponds, with varying evaporation times that can lead to differences in salinity and density. In this experiment, we used coagulants from these three ponds, labeled A, B, and C. Coagulant C, derived from the pond with the longest evaporation time, has the highest salinity of 310 ‰ and a density of 1.220 g/cm³. The mass of the tofu produced shows a consistent pattern among coagulants A, B, and C: an initial increase followed by a decrease, which is influenced by the salting-out and salting-in processes. When used at a volume of 15 mL, Coagulant C yielded the highest mass at 179.426 grams and the lowest water content at 71.152%, demonstrating its effectiveness in protein coagulation.